Elementary EFL Students’ Cognitive and Affective Responses to Visual Illustrations in English Sentence Construction - Lestari, Leady Karisma Putri; Baidawi, Achmad (Universitas Pahlawan Tuanku Tambusai, 2026)
Writing English sentences is challenging for elementary EFL students due to limited vocabulary, complex grammatical structures, and difficulties in generating ideas. This study explore fifth-grade students' responses to the use of visual illustrations in English sentence writing activities and how these illustrations help students understand context and construct sentences. This study used a qualitative descriptive approach involving 25 students and one English teacher. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed through data condensation, data display, and drawing/verifying conclusion. The findings show positive affective responses to the use of visual illustrations, such as increased motivation, enthusiasm, and confidence in writing English sentences. Cognitively, visual illustrations helped students understand context, generate ideas, and construct sentences more easily. However some students experienced difficulties interpreting the meaning of the illustrations and generating ideas, indicating differences in learning styles and the need for additional teacher guidance. These findings suggest that visual illustrations support students’ both emotional engagement and cognitive development when supported by appropriate instructional guidance.